Trawling disturbance effects on the trophic ecology of two co-generic Astropectinid species - MANGANO, M. C.; KAISER, M. J.; PORPORATO, E. M.D.; LAMBERT, G. I.; SPANÒ, N. (Mediterranean Marine Science, 2015)
<!--[if gte mso 9]> <![endif]--> Physical disturbance by trawling can have both negative and positive effects on populations of scavenging benthic organisms. In the present study the impact of fishing activity on feeding behaviour of the two Astropectinids, Astropecten bispinosus and A. irregularis, was assessed based on stomach contents analysis. The study was carried out along trawled seabed highlighting the positive response of the two facultative scavengers to carrion generated by trawl disturbance. Furthermore, there was greater food specialization in areas that were more heavily exploited by trawling. This specialisation could be linked to the availability of certain prey that results from the passage of fishing gears across the seabed. Interestingly, differences between the two species analysed have been highlighted in term of population dynamic, feeding rate, diet composition and diet diversity, testifying their capacity to coexist in the same fishing grounds. <!--[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Κανονικός πίνακας"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->